Heme A1M'ed at the kidney in sickle cell disease - Saraf, Santosh L. (Blood, 2020)
In this issue of Blood , Ofori-Acquah et al investigate hemolysis, hemopexin deficiency, and kidney function in sickle cell disease (SCD) and report that (1) acute elevations in heme lead to kidney damage in hemopexin-deficient states, and (2) a compensatory rise in α-1 microglobulin (A1M) relative to hemopexin concentration is associated with acute kidney injury. 1